N6-Methyladenosine-Related Gene Signature Associated With Monocyte Infiltration Is Clinically Significant in Gestational Diabetes Mellitus - Du, Runyu; Li, Ling; Wang, Yanjun (Frontiers in Endocrinology, 2022)
Objective: The objective of this study was to reveal the potential crosstalk between immune infiltration and N6- methyladenosine (m6A) modification in the placentas of patients with gestational diabetes mellitus (GDM), and to construct a model for the diagnosis of GDM. Methods: We analyzed imbalanced immune infiltration and differentially expressed m6A-related genes (DMRGs) in the placentas of patients with GDM, based on the GSE70493 dataset. An immune-related DMRG signature, with significant classifying power and diagnostic value, was identified using a least absolute shrinkage and selection operator (LASSO) regression. Based on the selected DMRGs, we developed and validated a nomogram model using GSE70493 and GSE72772 as the training and validation sets, respectively. Results: Infiltration of monocytes was higher in GDM placentas than in control samples, while the infiltration of macrophages (M1 and M2) in GDM placentas was lower than in controls. A total of 14 DMRGs were strongly associated with monocyte infiltration, seven of which were significant in distinguishing patients with GDM from normal controls. These genes were CD81, CFH, FABP5, GBP1, GNG11, IL1RL1, and SLAMF6. The calibration curve, decision curve, clinical impact curve, and receiver operating characteristic curve showed that the nomogram recognized GDM with high accuracy in both the training and validation sets. Conclusions: Our results provide clues that crosstalk between m6A modification and immune infiltration may have implications in terms of novel biomarkers and therapeutic targets for GDM.